Improvisation and the Making of American Literary Modernism. - Wallace, Rob, 1976- (Continuum International Pub. Group, 2010)
Improvisation, despite its almost ubiquitous presence in many art forms, is notoriously misunderstood and mysterious. Although earlier strands of American philosophy and art emphasized what might be called improvisational practices, it was during the modernist period that improvisational practice and theory began to make a significant impact on art and culture, specifically via the African American musical forms of jazz and blues. This musical development held important consequences for the larger artistic, cultural, and political life of America as a wholeGÇöand, eventually, the world. The hi.